Analysis Of Symbolic Value In Purchasing Imitation Louis Vuitton Bags: Economic Sociology Perspective - Zikri Sharu Ramadhan; Ricardi S. Adnan (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This research aims to explain the symbolic value in influencing the business of buying imitation Louis Vuitton bags which is seen using Beckert's (2009) four market valuation criteria. Based on a survey conducted by the Indonesian Anti-Counterfeiting Society (MIAP), economic losses due to imitation goods in Indonesia continue to increase every year until reaching a peak in 2014 of 65.1 billion rupiah, in 2020 it was recorded at 291 trillion, with a tax loss of 967 billion rupiah and employment of more than 2 million. Control over counterfeit goods is getting stricter. As explained by Cicilia King, Communications Manager for Louis Vuitton (Indonesia), especially in Europe, the company provides education, including to officers at airports, so that they are able to identify whether an item is genuine or fake. Louis Vuitton, according to various records, is the most counterfeited famous brand ( Kompas.com ). Young consumers are increasingly buying imitation products from luxury brands. Because late childhood is a time of searching for identity and a time of change (Asyia et al., 2022; Sofianita, 2015). This research uses Beckert's theory in the article The social order of markets (2009). Researchers used a qualitative approach with a case study type of research. The findings in this research explain that market valuation criteria consisting of standardization, cognitive anchoring, normative legitimacy, and social positioning are explained in this case study. KEYWORDS : Symbolic Value, Imitation, Louis Vuitton, Qualitative, Case Study